1999
DOI: 10.1021/la981062u
|View full text |Cite
|
Sign up to set email alerts
|

Lead and Zinc Retention during Hydration of Tri-Calcium Silicate:  A Study by Sorption Isotherms and 29Si Nuclear Magnetic Resonance Spectroscopy

Abstract: In cement-based materials heavy metals contents are rarely larger than a few hundred parts per million. Sorption isotherms of Zn(II) and Pb(II) carried out on nonhydrated (C3S) and hydrated (C-S-H) calcium silicate show that lead and zinc have different affinities for calcium silicate in a concentration range lower than the saturation concentration values of PbO and calcium zinc hydroxide. Lead has a much higher affinity than zinc for both nonhydrated and hydrated calcium silicate. Furthermore, the different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
43
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 33 publications
9
43
1
Order By: Relevance
“…From sorption experiments by Ludwig et al [94], it appears that Zn is strongly retained by CSH. This retention has been attributed to the linkage of tetrahedral Zn to CSH tetrahedral silicate chains [54] [82].…”
Section: Zincmentioning
confidence: 99%
“…From sorption experiments by Ludwig et al [94], it appears that Zn is strongly retained by CSH. This retention has been attributed to the linkage of tetrahedral Zn to CSH tetrahedral silicate chains [54] [82].…”
Section: Zincmentioning
confidence: 99%
“…Direct evidence showed that Pb in the investigated S/S samples was mainly incorporated into C-S-H phases. Moulin et al (1999) employed 29 Si NMR and EXAFS to demonstrate the presence of Si-O-Pb in the C-S-H species. Cocke (1992) and Badreddine et al (2004) have also reported fixation of Pb by C-S-H under 29 Si NMR and SEM-EDS analysis.…”
Section: Cement Treatmentmentioning
confidence: 99%
“…The most commonly-applied pozzolanic materials are portland cement, lime, and/or fly ash (Palomo & Palacios 2003, Dermatas & Meng 2003, Terzano et al 2005. The pozzolanic-based S/S techniques immobilize contaminants by adsorption, incorporation into the pozzolanic products (e.g., calcium alumina hydrate C-A-H or calcium silicate hydrate C-S-H), or via precipitation as metal hydroxides under alkaline pH associated with cement and lime (Gougar et al 1996, Moulin et al 1999. Physical entrapment of heavy metals adsorbed to particle surfaces in a low permeability cementitious matrix is also very likely (Moulin et al 1999, Badreddine et al 2004.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Zn substitution occurs either by replacement of Ca 2? or by direct linkage to the end of the silicate chains through Zn-O-Si bonds (Moulin et al 1999;Rose et al 2001). Moreover, the formation of Zn 6 Al 2 (OH) 16 CO 3 Á4H 2 O and CaO[Zn(OH) 2 ]Á2H 2 O have been reported when the Zn(OH) 2 was blended with PC (Qiao et al 2007).…”
Section: Introductionmentioning
confidence: 99%